The end of utopia politics and culture in an age of apathy - Jacoby, Russell (New York, NY Basic Books, 1999)
In The End of Utopia, Jacoby takes a sobering look at the future of politics. He points to the abandonment of utopian ideals that once sustained dissent and movements of social change.
The end of the end of the end of ideology -- The myth of multiculturalism -- Mass culture and anarchy -- Intellectuals; from utopia to myopia -- Thick aestheticism and thin nativism -- Retail sanity and wholesale madness.
Includes bibliographical references (pages 183-224) and index.
Keywords: Intellectuals -- United States; Politics and culture -- United States; Liberalism -- United States; Cultural pluralism -- United States; United States -- Intellectual life -- 20th century; United States -- Social conditions -- 1980- .